“Normal Children” and “Sick Feelings” in Greek Pedagogical Discourse during the Interwar Period, 1911–1939 - Karakatsani, Despina; Nikolopoulou, Pavlina (The Historical Review/La Revue Historique, 2022)
in the early twentieth century, pedagogy, both as theory and practice, was revisited under the influence of two important reform movements. Pedagogy, a newly emerging discipline, established itself as an academic field and placed children, and their needs and experiences, at the core of its research. in greece, the attempt to study the physical and mental development of children was closely linked with the attainment of national goals. This article looks into the attempt of interwar greek educators to delineate and demarcate “normality” and “morbidity” with regard to the development and expression of feelings during childhood. we examine how contemporary sociopolitical conditions, as well as eugenics, influenced not only the scientific discourse on “pathological” emotions but also the ways a new signification model of “normal” and “anomalous” child emotions impacted public discourse on education and the development of the educational system in greece.